Multi-threshold window discriminator based on SAR logic. (1st January 2022) - Jirsa, J.; Marcisovsky, M.; Jakovenko, J.
Abstract: The new X-ray imaging detectors allow capturing an X-ray image in various photon energy ranges in one shot. This technique is called X-ray color imaging, and it is becoming a promising method in fields such as medical imaging, computed tomography, and non-destructive material testing. To measure the energy spectrum in one shot, discriminant circuits need to be integrated into the pixel front-end electronics. Several solutions of in-pixel discriminators exist. However, current designs suffer from a low number of discrimination bins and need to adjust each threshold separately, leading to relatively complicated calibration procedures. This work introduces a novel design of a multi-threshold window discriminator based on successive approximation register logic. This circuit realizes in-pixel binning to ten equidistant windows. Two variables are used for tuning the multi-threshold window discriminator: offset of the first window and width of the windows. Setting these parameters allows the user to fulfill the need of the target application.